Optimizing practice guidelines through incorporating patient and family values and preferences. Issue 1 (February 2021) - Mitra, Souvik; Dorling, Jon; Johnston, Bradley C.
Abstract: Neonatal care largely follows clinical practice guidelines and position statements developed locally by respective institutions as well as by national and international organizations. One might expect that adoption of clinical guidelines based on best available research evidence would make neonatal care practices mostly uniform. However, wide variation in clinical practice is still noted in neonatal care. Neonatal clinical guidelines are developed almost exclusively by healthcare professionals, with little or no input from families of the infants being cared for. Therefore, such variation in practice may stem not only from how the evidence is interpreted but also how caregivers and families value different outcomes that are affected by particular interventions. Acknowledging and incorporating the variability in patient and family values and preferences in clinical guidelines is an important step towards allowing shared decision making while reducing unwarranted practice variation, and thereby helping clinicians practice family-centered evidence-based medicine.